Economic stimulus effects of product innovation under demand stagnation - Daisuke Matsuzaki; Yoshiyasu Ono (Osaka University, Institute of Social and Economic Research (ISER), 2023)
When faced with economic stagnation, innovation, product innovation in particular, is often cited as an effective stimulus because it is thought to encourage household consumption and lead to higher demand. Using a secular stagnation model with wealth preference, we examine the effects of product innovation on employment and consumption. Two types of product innovation are examined: quantity-augmenting-like innovation and addictive innovation. The former works as if a larger quantity were consumed although the actual quantity remains the same. The latter reduces the elasticity of the marginal utility of consumption. We find that the former reduces both consumption and employment whereas the latter expands them.
Keywords: O33; E31; E24; 330; demand stagnation; product innovation; consumer price index; economic stimulus